MORPHOLOGICAL AND MERISTIC STUDY ON RICE BUGS Leptocorisa oratorius (Fabricius, 1764) AT KUALA PILAH AND BAHAU PADDY FIELDS - NorJasmin Hussin; Izzati Adilah Azmir (Journal of Academia, 2022)
One of the major pests found in paddy field is the rice bug, Leptocorisa oratorius that feeds on the panicle of the rice. Leptocorisae species are typically found in paddy fields and lowland grass areas according to their adaptations. This rice bug is the major sap sucking pest of paddy and causes serious problems in the cultivation of the crop. Thus, this study urged to identify the species of specimens collected in the paddy fields of Kuala Pilah and Bahau through morphological and meristic characteristics using key pictorial evidence of Leptocorisa oratorius. There were seven morphometric characteristics measurements obtained and four meristic characteristics observed using a dissecting microscope. A total of 308 samples of Leptocorisa oratorius (Hemiptera: Alydidae) collected from two different areas in selected paddy fields of Kuala Pilah known as Kampung Kuala Serdang and Kampung Lonek. All the morphometric characters were significantly different (P<0.05) except for the antenna (p= 0.346) and hindlegs (p= 0.117). Moreover, the spots on the abdomen at ventral-lateral, and behind the compound eye are unique and could not be seen in any other Leptocorisae sp. Subsequently, the identification was supported by constructing key pictorial which later recognized these specimens as L. oratorius. The standard error of all morphometric characteristics revealed small values and slight differences in the body length and the wings between these two populations. The high abundance of L. oratorius found in milking stage of paddy compared to soft dough stage will jeopardize the paddy yield. Believably, this study can help to create awareness to the farmers and researchers to find solutions to defend the paddy crop against pests.